Technopreneur produces gluten-free flour for the Al-Muawanah Tasikmalaya Cooperative - Hamdani, Aam; Komaro, Mumu; Rahmawati, Yulia; Mahmudatussa’adah, Ai (Jurnal Abmas, 2026)
The growing trend of healthy lifestyles and increasing awareness of health conditions such as celiac disease have driven global demand for gluten-free food products. Al Muawanah Cooperative in Tasikmalaya has great potential in utilizing local resources such as cassava, bananas, and breadfruit to create market opportunities. This article aims to design a Technopreneurship-based business model for producing gluten-free flour among cooperative members. The Technopreneurship approach is integrated throughout the value chain, from production using standardized, simple equipment to digital marketing through social media and e-commerce platforms to effective cooperative management. The implementation method consists of three main stages: preparation (feasibility study and training), implementation (production and marketing), and evaluation. The results of the discussion indicate that this model not only has the potential to increase members’ incomes through the sale of high-value-added products but also to empower them with digital and entrepreneurial skills relevant to the modern economy. It is concluded that adopting a Technopreneurship concept in gluten-free flour processing is a feasible and sustainable strategy to enhance the cooperative's competitiveness and economic independence.
Keywords: community empowerment; digital marketing; gluten-free flour production; technopreneurship